Integrasi LKPD Berbasis Etnomatematika Rumah Bolon Batak Toba Terhadap Hasil Belajar Geometri Siswa di SMP - Sinaga, Amrinaldo; Tambunan, Hardi; Pangaribuan, Firman (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to determine the effect of using ethnomathematics-based LKPD Rumah Bolon Batak Toba on the geometry learning outcomes of junior high school students. The research uses a quantitative approach with a quasi-experimental design type pretest–posttest control group design. The research subjects consist of two classes, namely the experimental class and the control class, each comprising 20 students. Data were obtained through pretest and posttest, then analysed using normality test, homogeneity test, Independent Samples t-test, and N-Gain analysis. The analysis results show that the data are normally distributed and homogeneous. The t-test on posttest scores and N-Gain showed a significance value of 0.000 < 0.05, indicating a significant difference in results and learning improvement between the experimental and control classes. Therefore, it can be concluded that the use of ethnomathematics-based LKPD Rumah Bolon Batak Toba has a significant effect on improving learning outcomes. Thus, it can be concluded that the use of ethnomathematics-based LKPD of the Batak Toba Bolon House has a significant effect on improving the geometric learning outcomes of junior high school students.